The heritage of normal school graduate teachers in the configuration of the folkloric field in Chiloé. Teachers, cultores and folklorists - Yáñez Aguilar, Cristian (Revista Musical Chilena, 2021)
From the mid-1960s to the 1980s, Teachers’ Folkloric groups emerged in Chiloé during a fruitful period that began to decline in the mid-90s. These groups carried out an intense cultural activity based on the social sciences and the artistic projection, reproducing a set of theoretical concepts related to folklore that were fundamental for the configuration of this cultural field in this province of the south of Chile. The objective of this work is to document, through a contextual analysis, the contribution of rural teachers in the configuration of this cultural field by approaching the genres and concepts that guided their actions. From a methodological point of view, we have worked based on bibliographic documentation, interviews and analysis of sounds and audiovisual records. The study has as horizon to collaborate in the understanding of the folkloric music’s recent history, providing a critical and comprehensive perspective.